2017
DOI: 10.1021/acs.langmuir.7b01942
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Driven Parallel and Antiparallel β-Sheet Secondary Structures of Phe–Ala Lipodipeptides

Abstract: Four Phe-Ala lipodipeptides with different stereochemical structures are observed to self-assemble into twisted nanoribbons in water. The handedness of the twisted nanoribbons is controlled by the chirality of the phenylalanine near the alkyl chain, while the stacking handedness of the phenyl and carbonyl groups is determined by the alanine at the C-terminal. The homochiral and heterochiral lipodipeptides self-assemble into parallel and antiparallel β-sheet structures, respectively. The H NMR, FTIR, X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…The absorption band of amide A ( v N–H ) was identified at 3270 cm −1 . Besides, the absorption bands of amide I ( v C═O ) were identified at 1631 and 1627 cm −1 ; a parallel β ‐sheet structure should be formed . Moreover, absorption bands at around 1450 cm −1 , which probably originated from the partially deuterated N–H groups as well as the overlap of ring stretching vibration of phenylene groups, bending vibration of –CH 3 , –OH, and HOD, could also be identified.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band of amide A ( v N–H ) was identified at 3270 cm −1 . Besides, the absorption bands of amide I ( v C═O ) were identified at 1631 and 1627 cm −1 ; a parallel β ‐sheet structure should be formed . Moreover, absorption bands at around 1450 cm −1 , which probably originated from the partially deuterated N–H groups as well as the overlap of ring stretching vibration of phenylene groups, bending vibration of –CH 3 , –OH, and HOD, could also be identified.…”
Section: Resultsmentioning
confidence: 99%
“…42 With our further investigation of heterogeneous lipodipeptides, the side group steric hindrance of peptide backbones and the stereochemical sequence of peptide segments were found to directly affect the molecular packing and chiral stacking of chromophores. 32,34 Additionally, for Gly-Ala-Ala lipotripeptides, our research indicated that the chirality of the central alanine residue determined the handedness of self-assemblies and the hydrogen bonding formed by the amide group of central alanine moiety was thought to play an important role in the self-assembly. 43 Herein, we further expand our research into the selfassembly of Ala-Ala-Ala lipotripeptides.…”
Section: ■ Introductionmentioning
confidence: 84%
“…39 Further studies revealed that the molecular packing structures also played an important role in the handedness of the organic self-assemblies. 40 For some tripeptides composed of phenylalanine and valine, the molecular packing handedness was found to be dominated by the chirality of the central amino acid. 41,42 It is well documented that the methyl group plays a vital role in biological science.…”
Section: Introductionmentioning
confidence: 99%